Conceptual and Curricular Dimensions of ’Abduh’s Educational Reform - Shafie, Ahmad Bazli (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Conceptual and Curricular Dimensions of ’Abduh’s Educational Reform